Design of Integrated Distillation-Dehydration Prototype for Bioethanol with Flexible Column and Capillary Condenser - Mustofa; Siradjuddin Haluti; Ovin Daud (Logic : Jurnal Rancang Bangun dan Teknologi, 2025)
The production of high-purity bioethanol remains a challenge, particularly when the feedstock originates from traditional fermentation processes such as cap tikus. This study presents an integrated distillation–dehydration prototype that enables simultaneous vapor separation and moisture removal within a single columnn – an innovation that combines a flexible dual-layer adsorbent chamber and a capillary-type condenser tio improve mass and heat transfer performance. The prototype consists of three main components: a boiler with a diameter and height of 500 mm, a distillation–dehydration column with a diameter of 101.6 mm and a height of 1000 mm designed for flexibility to accommodate various adsorbents, and a shell-and-tube condenser 1200 mm long equipped with 19 capillary tubes of 8 mm diameter. Heat is supplied by a “1000-eye” gas burner that ensures uniform thermal distribution at the boiler base. Preliminary testing with 10.8 L of cap tikus (25% alcohol) produced 94 mL of distillate in 3 hours, with a stable of 5 °C temperature gradient along the column. The resulting distillate reached alcohol 87% purity, demonstrating the capability of the integrated system to enhance dehydration performance. Despite performance limitations caused by heat losses in the boiler and vapor-flow resistance witihn the zeolite-packed column, theprototype shows promising thermal and separation characteristics and is ready for futher optimization to increase distillation rate and energy efficiency.